Crisis, productive forces, and environmental issue: development and dependence in contemporary Bolivia - Gomes, Cláudia Maria Costa; Santos, Nivalter Aires dos; Santos, Janaina Freire dos (Argumentum, 2024)
This article debates the current crisis based on a critical interpretation of the contradictions of capitalism in Bolivia. The investigation methodology is based on the critique of political economy, and seeks to highlight the crisis of capital, expropriations, and the environmental issue. Bolivia was selected as the object of our reflection because its neo-extractivist strategy can not escape predatory forms of exploitation and expropriation. Due to the dynamics of the class struggle, the political road is uneven and, given the urgency of capital, the attacks to counter this predation need to be deepened. As such, we gain an understanding that the tendencies of capital accumulation on the periphery of capitalism have different forms, this despite the particularities of each country, such as coups d'état returning to the scene, as in the Bolivian case, but it is always based on the perception of democracy as an obstacle to capital.
Keywords: Crisis; Productive forces; Environmental issues; Dependence; Bolivia